FGF23, Frailty, and Falls in SPRINT. Issue 2 (1st December 2020) - Jovanovich, Anna; Ginsberg, Charles; You, Zhiying; Katz, Ronit; Ambrosius, Walter T.; Berlowitz, Dan; Cheung, Alfred K.; Cho, Monique; Lee, Alexandra K.; Punzi, Henry; Rehman, Shakaib; Roumie, Christianne; et al.
Abstract : BACKGROUND/OBJECTIVES: Chronic kidney disease (CKD) is associated with frailty. Fibroblast growth factor 23 (FGF23) is elevated in CKD and associated with frailty among non‐CKD older adults and individuals with human immunodeficiency virus. Whether FGF23 is associated with frailty and falls in CKD is unknown. DESIGN: Cross‐sectional and longitudinal observational study. SETTING: Systolic Blood Pressure Intervention Trial (SPRINT), a randomized trial evaluating standard (systolic blood pressure [SBP] <140 mm Hg) versus intensive (SBP <120 mm Hg) blood pressure lowering on cardiovascular and cognitive outcomes among older adults without diabetes mellitus. PARTICIPANTS: A total of 2, 376 participants with CKD (estimated glomerular filtration rate [eGFR] <60 mL/min/1.73 m 2 ). MEASUREMENTS: The exposure variable was intact FGF23. We used multinomial logistic regression to determine the cross‐sectional association of intact FGF23 with frailty and Cox proportional hazards analysis to determine the longitudinal association with incident falls. Models were adjusted for demographics, comorbidities, randomization group, antihypertensives, eGFR, mineral metabolism markers, and frailty. RESULTS: After adjustment, the odds ratio for prevalent frailty versus non‐frailty per twofold higher FGF23 was 1.34 (95% confidence interval [CI] = 1.01–1.77). FGF23 levels in the highest quartile versus the lowest quartile demonstrated more than a twofold increased fall risk (hazard ratio [HR] = 2.32; 95% CI = 1.26–4.26), and the HR per twofold higher FGF23 was 1.99 (95% CI = 1.48–2.68). CONCLUSION: Among SPRINT participants with CKD, FGF23 was associated with prevalent frailty and falls.